Dialektika Gaya Kepemimpinan Transformatif dan Madrasah Unggul dalam Perspektif Kebijakan Daya Saing Pendidikan Bermutu - Muwahid Shulhan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
ASEAN Economic Community is the era of globalization of the region. It is necessary to be observed the education in Indonesia carefully, so that Indonesian human resources are ready to face increasingly tight competition with other countries. Organizational culture at the school level requires leaders who are able to mobilize developments and changes that are doing creative activities, finding new strategies, methods, ways, or concepts in teaching so that learning is meaningful and giving birth to quality education. In this regard, it requires transformative leadership as an effort to produce a competitive education and produce learners who have integrity of personality, discipline, creative, innovative, and competitive attitude. The professionalism of educational leadership as a transformational leader needs to have competence, transparency, efficiency, and high quality. The Transformative Leadership Planning Strategy must be able to change the situation from ordinary to achieving by integrating and accommodating local-value-based jugglers, fostering human relationships by motivating subordinates, tut wuri handayani (humanist​), dynamic circumstances to elicit vision, initiative , and group creativity in innovation and improvement of madrasah (catalist) programs, ideas agent in innovation that give profit to all element of madrasah, especially for students' interests, Madrasah Principals and staff that have the capability of religious-cultural discourse in the form of local culture Javanese) and religious (Islam) are used for the achievement of madrasah objectives, so as to enable the implementation of cultural leadership role, the occurrence of mission communications, vision, values ​​and philosophy of madrasah to the community, parents and government in order to obtain support and partnership so that enabling the role of social leadership (social leadership).